Effect of Service Quality of Ncell on Customer Satisfaction - Khanal, Badrinath (Dibyajyoti Journal, 2025)
The objective of this study is to understand the effect of service quality dimension on the customer satisfaction of the Ncell users in Rupandehi. This research is of descriptive in nature. This research is descriptive in nature because it describes data and characteristics about the population being studied on the basis of statistics without any manipulation. The findings of this study are totally based on the primary survey. The study is based on various statistical tests and analysis. Descriptive statistics is used to calculate mean and standard deviation. Correlation and regression are calculated to analyze and interpret the data. For analysis, data are presented in table. For the study customers of Ncell are total population. Among the population, the sample size was 400 respondents. The sample size was determined by using convenience sampling method. The sample of the study were Ncell customers from Rupandehi area in Nepal, who using Ncell communication. This study shows that the correlation analysis indicates that dimensions of service quality reliability, responsiveness, assurance, and empathy are positively correlated but tangibility is negatively correlated with customer satisfaction in Ncell. The regression analysis highlights the influence of various service quality dimensions on customer satisfaction in Ncell. Empathy, reliability, assurance, and empathy are positively associated with customer satisfaction, with tangibility demonstrating the strongest effect. Furthermore, Ncell is a service oriented organization, hence providing continuous training to the employees on issues like courtesy, etiquette and communication skills while dealing with customers is of immense importance. Ncell is a customer oriented organization, hiring potential human resource is a must important and for this reason, the Ncell should hire self-motivated, enthusiastic employees who will like to deal with customer and will try to solve customer complaints and other issues in an effective manner.